Mononuclear and multinuclear salicylaldimine metal complexes as catalysts precursors in the oxidation of phenol and cyclohexene - Van Wyk, Juanita Lizélle (2014)
Philosophiae Doctor - PhD === In this thesis typical homogeneous and dendritic immobilized catalysts derived from salicylaldimines were investigated as catalysts for the oxidation of hydrocarbons using hydrogen peroxide as oxidant under aerobic conditions. This research work thus describes the synthesis of several new N-(aryl)salicylaldimines as well as peripheral functionalised salicylaldimine poly(propyleneimine) dendrimers. The dendritic ligands were obtained by modifying the peripheral groups of Generation 1 and Generation 2 poly(propyleneimine) dendrimer, (DAB-(NH2)n) which are commercially available. Both types of ligands were utilized to synthesize Cu(II) and Co(II) complexes using appropriate acetate salts. The ligands systems and metal complexes prepared were fully characterized using a range of physical techniques. The Cu(II) and Co(II) complexes were evaluated as catalysts for the oxidation of phenol and cyclohexene using hydrogen peroxide as oxidant under an oxygen atmosphere. The catalytic oxidation of phenol to the dihydroxybenzenes, catechol (CT) and hydroquinone (HQ), was investigated in aqueous media at various pH values. All the complexes investigated were active for the hydroxylation process producing CT as major product. The pH of the reaction medium was found to have much more of an influence on the activity and product selectivity of the Co(II) complexes as compared to the case for the Cu(II) complexes. All the catalysts investigated were also found to exhibit good activity for the oxidation of cyclohexene producing predominantly the allylic oxidation products 2-cyclohexene-1-one and 2-cyclohexene-1-ol. However the formation of the epoxide, cyclohexene oxide was also observed as minor product or in trace quantities. It was found that the cobalt catalysts produced 2-cyclohexene-1-one as major product, however higher levels of 2-cyclohexene- 1-ol was produced by all catalysts in catalytic runs where the oxidant to substrate ratio was reduced and when the metal loading was increased. In the case of the copper catalysts 2- cyclohexene-1-ol was produce in slightly higher levels than 2-cyclohexene-1-one.